2013
DOI: 10.1007/s00280-013-2112-2
|View full text |Cite
|
Sign up to set email alerts
|

Severe and prolonged lymphopenia observed in patients treated with bendamustine and erlotinib for metastatic triple negative breast cancer

Abstract: Purpose Triple negative breast cancers (TNBC) frequently have high epidermal growth factor receptor (EGFR) expression and are sensitive to DNA-damaging agents. Improved therapies are needed for this aggressive malignancy. Patients and methods We performed a phase I trial of bendamustine and erlotinib, an EGFR tyrosine kinase inhibitor, in patients with metastatic TNBC, ECOG performance status ≤2, and ≤1 prior chemotherapy for metastatic disease. Each 28-day cycle included intravenous bendamustine on days 1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 27 publications
(33 reference statements)
1
20
0
Order By: Relevance
“…Smaller phase 2 trials also reported high rates (80–90%) of grade 3 lymphopenia (Ogawa et al , ) during treatment with BR. These observations have also been replicated in patients receiving bendamustine for diffuse large B‐cell lymphoma (Ohmachi et al , ) and for non‐haematological malignancies (Layman et al , ), consistent with a direct pharmacological effect. In October 2017, the EMA issued a notification of increased risk of Pneumocystis jirovecii (PJP) infections and other opportunistic infections in the context of bendamustine combination therapy, recommending appropriate prophylaxis to be considered.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Smaller phase 2 trials also reported high rates (80–90%) of grade 3 lymphopenia (Ogawa et al , ) during treatment with BR. These observations have also been replicated in patients receiving bendamustine for diffuse large B‐cell lymphoma (Ohmachi et al , ) and for non‐haematological malignancies (Layman et al , ), consistent with a direct pharmacological effect. In October 2017, the EMA issued a notification of increased risk of Pneumocystis jirovecii (PJP) infections and other opportunistic infections in the context of bendamustine combination therapy, recommending appropriate prophylaxis to be considered.…”
mentioning
confidence: 69%
“…It is evident from our data that higher cumulative dose intensity (≥1080 mg/m 2 ) confers a higher risk of CD4+ lymphopenia without evidence for superior efficacy (Friedberg et al , ). Given the independent correlation of cumulative bendamustine dose with delayed CD4+ recovery, together with the possibility of a preferential impact of the drug on the CD4+ cell subset (Layman et al , ; Ogawa et al , ), we caution against employing bendamustine at cumulative doses ≥1080 mg/m 2 . As a practical measure, EOT ALC, perhaps reflecting individual drug sensitivity, may serve as a simple and reproducible biomarker to predict delayed CD4+ recovery after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Gefitinib (EGFR inhibitor) reduces cancer cell multiplication and enhances the cytotoxicities of carboplatin and docetaxel ( Figure 5) [70,71]. There are a number of different kinds of EGFR inhibitors trialed against TNBC such as the tyrosine kinase inhibitors (TKIs)-erlotinib and lapatinib along with the monoclonal antibodies (mAbs) such as cetuximab and panitumumab [72][73][74][75]. The reports of failures of EGFR-TKIs and mAbs, however, inspired combination therapy that includes mAbs and chemotherapeutics that proved to be a more efficacious.…”
Section: Epidermal Growth Factor Receptor (Egfr)mentioning
confidence: 99%
“…Lymphocytopenia is a common side effect among various types of chemotherapies and can even be caused by the cancer itself. Several chemotherapies have been known to cause lymphocytopenia including temozolomide [71], everolimus [72], bendamustine [73], erlotinib [73], various purine analogs [74], and various cytotoxic chemotherapies [75]. Lymphocytopenia has the potential to reduce the body's own ability to eliminate cancer cells naturally, thus reducing the effectiveness of chemotherapy.…”
Section: Neutropenia and Lymphocytopeniamentioning
confidence: 99%